The Process of Mathematical Literacy in Middle School Students: Analyzing the Role of Mathematical Dispositions - Nurhayati, Hanifah; Hasanah, Aan; Fitriyah, Yuni; Febrianti, Tri Sedya (Jurnal Pendidikan MIPA, 2024)
Mathematical literacy extends beyond solving equations to applying mathematical concepts in everyday life. This study investigated the development of mathematical literacy and the challenges students face, analyzed through their mathematical dispositions. A qualitative case study methodology was employed, utilizing a PISA-equivalent test, a mathematical disposition questionnaire, and interviews. 40 7th-grade students were classified into high, moderate, and low disposition groups, with a detailed analysis of three representative students from each group. The Results indicated that students with high mathematical dispositions solved problems effectively, students could formulate the mathematical problem, apply mathematical concepts, and interpret real-world outcomes. Conversely, those with moderate and low dispositions struggled to apply relevant concepts and could only identify given information for problem-solving. These challenges are associated with a lack of understanding of fundamental concepts, particularly proportional reasoning. Factors such as motivation, interest, self-confidence, and attitudes toward mathematics significantly influence students' dispositions and their mathematical literacy skills.         Keywords: mathematical literacy, mathematical literacy process, mathematical disposition. DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp893-913